The Performance of a National Logistics Company Measured by Dynamic Capabilities And Innovation Performance: Literature Review - Zainul Wasik; Kuncoro Catur Nugroho; MahjudinMahjudin; Dody Suhermawan (PT. Mawadaku Sukses Solusindo, 2023)
ABSTRACTIntroduction: National logistics service companies require an integrated approach to business development both to maintain the loyalty of current customers and to reach new customers, so they can work on this prospective market more optimally. To meet these demands, an increase in the company's dynamic capabilities and competencies in producing sustainable innovations is urgently needed so that it can drive the company's performance in total.Objective: The basic problem discussed in this study is how is the relationship between dynamic capability, innovation performance, and company performance in the national logistics service industry.Design/Methodology/ Approach: The research uses a literature study method related to aspects of dynamic capabilities, innovation performance, and company performance. Based on the literature study, a relationship pattern between these factors is then made as a framework for further research.Findings: That there is a direct relationship between dynamic capabilities (dynamic capabilities) with innovation performance. Variables for dynamic capabilities include adaptive capabilities, absorptive capabilities, and innovative capabilities. While the relationship between dynamic capabilities and company performance can be directly or indirectly through innovation performance.Research Implications: This research is expected to provide input or guidance for managers in making a strategic policy in a logistics company that dynamic capabilities affect the innovation performance of a company. In addition, dynamic capabilities can directly influence company performance, and innovation performance can affect company performance.